Art Education Management Optimizes Early Age Potential: Kamsidjo Budi Utomo Kamsidjo123@gmail.com Lecturer in the Fine Arts Department UNNES - Universitas Negeri Semarang - Kamsidjo Budi Utomo (Universal Journal, 2020)
Early childhood education is a form of education that focuses on laying the foundation for physical growth and development (fine and gross motor coordination), intelligence (power of thought, creativity, emotional intelligence, spiritual intelligence), socio emotional (attitude and behavior and religion) language and communication, in accordance with the uniqueness and stages of development that are passed by early childhood. (Adalilla, S, 2010) [1]We can also apply art to education. Through art we can provide alternatives for the development of the psychic potential of the self and can act as liberating soul cathars. So art education is also able to facilitate the needs of children to maximize their growth and development.